Research on Kinematics and Stability of a Bionic Wall-Climbing Hexapod Robot - Shoulin Xu; Bin He; Heming Hu (Applied Bionics and Biomechanics)
Wall-climbing hexapod robot as a bionic robot has become a focus for extensive research, due to a wide range of practical applications. The most contribution of this paper is to analyze the kinematics and stability of a wall-climbing hexapod robot, so as to provide a theoretical basis for the stable walking and control of the robot on the wall. Firstly, the kinematics model of the wall-climbing hexapod robot is established based on the D-H method. Then, in order to keep the robot from tipping over, the stability of the wall-climbing hexapod robot is analyzed in depth, obtaining the critical condition which makes the robot to tip over. Afterward, the kinematics simulation of the wall-climbing hexapod robot is operated to analyze motion performances. Finally, the experiments are used to validate the proposed kinematics model and stability. The experimental results show that the kinematics model and stability condition of the wall-climbing hexapod robot are correct.